Studying the Humoral Response against SARS-CoV-2 in Cuban COVID-19 Recovered Patients - Ivette Orosa Vázquez; Marianniz Díaz; Yaima Zúñiga Rosales; Klayris Amada; Janoi Chang; Ernesto Relova Hernández; Yaima Tundidor; Hilda Roblejo Balbuena; Giselle Monzón; Bárbara Torres Rives; Enrique Noa Romero; Danay Carrillo Valdés; et al. (Journal of Immunology Research, 2024)
Understanding the immune response generated by SARS-CoV-2 is critical for assessing efficient therapeutic protocols and gaining insights into the durability of protective immunity. The current work was aimed at studying the specific humoral responses against SARS-CoV-2 in Cuban COVID-19 convalescents. We developed suitable tools and methods based on ELISA methodology, for supporting this evaluation. Here, we describe the development of an ELISA for the quantification of anti-RBD IgG titers in a large number of samples and a similar test in the presence of NH4SCN as chaotropic agent for estimating the RBD specific antibody avidity. Additionally, a simple and rapid ELISA based on antibody-mediated blockage of the binding RBD-ACE2 was implemented for detecting, as a surrogate of conventional test, the levels of anti-RBD inhibitory antibodies in convalescent sera. In a cohort of 273 unvaccinated convalescents, we identified higher anti-RBD IgG titer (1 : 1,330, p <0.0001) and higher levels of inhibitory antibodies blocking RBD-ACE2 binding (1 : 216, p <0.05) among those who had recovered from severe illness. Our results suggest that disease severity, and not demographic features such as age, sex, and skin color, is the main determinant of the magnitude and neutralizing ability of the anti-RBD antibody response. An additional paired longitudinal assessment in 14 symptomatic convalescents revealed a decline in the antiviral antibody response and the persistence of neutralizing antibodies for at least 4 months after the onset of symptoms. Overall, SARS-CoV-2 infection elicits different levels of antibody response according to disease severity that declines over time and can be monitored using our homemade serological assays.